Fluorine-containing fullerenes and endometallofullerenes: synthesis, structure, and spectroscopic characterization - Shustova, Natalia Borisovna, author; Strauss, Steven H., advisor; Anderson, Oren P., committee member; Szamel, Grzegorz, committee member; Elliott, Cecil Michael, committee member; Roess, Deborah A., committee member (Colorado State University. Libraries, 2010)
Many new members of a relatively new class of exohedral fullerene derivatives with fluorine-containing electron-withdrawing groups have been prepared and studied by spectroscopic methods and X-ray crystallography. The fluorination and/or perfluoroalkylation reactions were performed with C60, C70, the higher hollow fullerenes C60+m (m = 14, 16, 18, 20, and 22), the endohedral metallofullerene Sc3N@C80-Ih(7), and the azafullerene dimer (C59N)2. Several efficient synthetic methods have been developed for perfluoroalkylation, which involved high-temperature reactions with AgCF3CO2 and with thermally or photochemically activated reactions with RFI reagents (RF = CF3, C2F5, n-C3F7, i-C3F7, n-C4F9, and n-C6F13). Structural studies of the C60(RF)n and C70(RF)n products demonstrated that variation of the size and structure of the RF radical led to the formation of derivatives with unprecedented addition patterns and hence unprecedented properties. Many of these derivatives were shown to have superior electron-accepting properties. Trifluoromethylation of a sample of insoluble hollow higher fullerenes resulted in the structural characterization of several new dodecakis(trifluoromethyl) fullerene compounds, and this led to the first experimental observation of fullerenes C74-D3h and C78-D3h(5). In the case of trifluoromethylation of (C59N)2, a strong effect of the heteroatom on the addition patterns of the products was discovered. The first X-ray crystal structure of a single regioisomer of C59N(CF3)5, as well as spectroscopic studies of C59N(CF3)7,9,11, revealed unexpected addition patterns which resemble that of Cs-C60X6 derivatives. The isolation and characterization of seventeen Sc3N@(C80-Ih)(CF3)n (even n = 2-16) compounds, including the X-ray structures of Sc3N@(C80-Ih(7))(CF3)10, Sc3N@(C80-Ih(7))(CF3)12, Sc3N@(C80-Ih(7))(CF3)14, and Sc3N@(C80-Ih(7))(CF3)16, have demonstrated for the first time a strong mutual effect of (i) the presence of the Sc3N cluster on the addition pattern and (ii) the addition pattern on the position of and structure of the Sc3N cluster.
Keywords: fullerenes; fluorine; crystallography; Fullerenes -- Synthesis; Fluorine compounds -- Synthesis; Radiation chemistry; X-ray crystallography -- Research